EFFICACY OF IMMUNOSUPPRESSIVE THERAPY IN CONNECTIVE TISSUE DISEASE-ASSOCIATED ILLNESS: SYSTEMATIC REVIEW - HABTAR, GHADAH FAISAL (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background: Connective tissue diseases (CTDs), such as systemic lupus erythematosus (SLE), systemic sclerosis (SSc), and rheumatoid arthritis (RA), frequently lead to severe complications like interstitial lung disease (ILD) and pulmonary arterial hypertension (PAH). Immunosuppressive therapy (IS) is a cornerstone of treatment, but its efficacy and safety across different CTD subtypes remain uncertain. Objective: This systematic review evaluates the efficacy and safety of IS in CTD-associated ILD and PAH, focusing on clinical outcomes, pulmonary function, hemodynamic improvements, and adverse events. Methods: Following PRISMA guidelines, we conducted a comprehensive literature search across PubMed/MEDLINE, Embase, Web of Science, and Cochrane Library. Eligible studies included randomized controlled trials, cohort studies, and case-control studies assessing IS in CTD-ILD or CTD-PAH. Data were extracted and synthesized narratively due to heterogeneity. Results: Seven studies (n = 13–16,562 participants) were included. IS improved hemodynamics in CTD-PAH, with early initiation reducing mortality (8.8% vs. 22.9%). Nintedanib combined with IS stabilized lung function in CTD-ILD (61.1% with stable/improved HRCT). However, long-term IS increased non-melanoma skin cancer risk (OR 1.69) and high-dose IS raised invasive fungal infection risk (3.8%). Conclusion: IS is effective in CTD-PAH and CTD-ILD, particularly when initiated early or combined with antifibrotics. However, infection and malignancy risks necessitate careful patient selection. CTD subtype-specific treatment strategies are recommended.